Shared care arrangements for specialist drugs in the UK: the challenges facing GP adherence. Issue 6 (16th June 2010) - Crowe, Sarah; Cantrill, Judith A; Tully, Mary P
Abstract : Objective: To explore the challenges facing GPs' adherence to shared care arrangements for specialist drugs. Design: A qualitative study using semistructured interviews; data analysed using the 'framework' approach aided by QSR N-Vivo 2.0. Setting: Three Primary Care Trusts (PCTs) within one Strategic Health Authority (SHA) in the North West of England. Participants: 47 semistructured interviews were conducted with a range of Practice, PCT and SHA staff and other relevant stakeholders. Results: GPs faced multiple challenges in adhering to shared care arrangements for specialist drugs. Psychiatric patients were given as an example where such arrangements were perceived as particularly difficult to maintain, with patient non-compliance a contributory factor. GP uncertainty and confusion surrounded the sharing of test results between primary and secondary care, and was felt to give rise to test duplication and omission. Of particular concern to GPs was the lack of compliance of practice and hospital colleagues with these arrangements, and the dependence they placed on specialists' responses to requests for advice. Conclusion: This study provides evidence of the numerous challenges facing GP adherence to shared care arrangements. Such challenges need to be overcome if the issues of test duplication and omission are to be addressed, and GPs' future acceptance of shared care arrangements encouraged.